2017
DOI: 10.3389/fnmol.2017.00022
|View full text |Cite
|
Sign up to set email alerts
|

APP as a Protective Factor in Acute Neuronal Insults

Abstract: Despite its key role in the molecular pathology of Alzheimer’s disease (AD), the physiological function of amyloid precursor protein (APP) is unknown. Increasing evidence, however, points towards a neuroprotective role of this membrane protein in situations of metabolic stress. A key observation is the up-regulation of APP following acute (stroke, cardiac arrest) or chronic (cerebrovascular disease) hypoxic-ischemic conditions. While this mechanism may increase the risk or severity of AD, APP by itself or its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
56
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 223 publications
(273 reference statements)
0
56
1
Order By: Relevance
“…Importantly, this finding was not causally related to endocrine status because both wt and arcAβ mice responded similarly to an acute stressful challenge. How Aβ oligomers or other aspects of the hAPParc/swe genotype modulate the impact of stress is worth investigating in the future, but one possible explanation may be provided by Aβ itself: in its physiological role, Aβ has synapto‐protective effects and is generated in response to excitatory stress, such as after physical impact, ischaemia or chronic stress (Giuffrida et al., ; Hefter & Draguhn, ; Hick et al., ; Kögel, Deller, & Behl, ; Palop & Mucke, ; Roselli, ). Thus, abundant, but not excessive, Aβ oligomers in young arcAβ mice may have protected post‐synaptic synapses from overexcitation, and subsequent downregulation, by chronic stress, preventing attentional decline.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this finding was not causally related to endocrine status because both wt and arcAβ mice responded similarly to an acute stressful challenge. How Aβ oligomers or other aspects of the hAPParc/swe genotype modulate the impact of stress is worth investigating in the future, but one possible explanation may be provided by Aβ itself: in its physiological role, Aβ has synapto‐protective effects and is generated in response to excitatory stress, such as after physical impact, ischaemia or chronic stress (Giuffrida et al., ; Hefter & Draguhn, ; Hick et al., ; Kögel, Deller, & Behl, ; Palop & Mucke, ; Roselli, ). Thus, abundant, but not excessive, Aβ oligomers in young arcAβ mice may have protected post‐synaptic synapses from overexcitation, and subsequent downregulation, by chronic stress, preventing attentional decline.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, APP participates in a number of important functions in the brain, including synaptic function and cellular response to stress (Panegyres ). Numerous studies have suggested that APP is a neuroprotective factor in acute neuronal insults, including acute hypoxia‐ischemia, traumatic brain injury and excitotoxicity (Hefter and Draguhn ). Our data demonstrated that MCAO induced evident decrease in APP level compared with the sham‐control at 6 h, whereas Tan‐67 treatment attenuated MCAO‐induced APP decrease and this effect could be reversed by naltrindole.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its key role in the molecular neuropathology of AD, increasing evidence indicate that APP is a neuroprotective factor in acute ischemic stroke (Hefter and Draguhn 2017). On the other hand, ischemic stroke also alters APP expression and processing (Hiltunen et al 2009).…”
mentioning
confidence: 99%
“…APP is a single‐pass transmembrane, highly pleiotropic protein involved in numerous cellular functions, such as iron transport, cell and synaptic adhesion, homeostasis, and apoptosis . APP is ubiquitously expressed as multiple splice variants, which undergo extensive post‐translational modification .…”
Section: Introductionmentioning
confidence: 99%
“…APP is a single-pass transmembrane, highly pleiotropic protein involved in numerous cellular functions, such as iron transport, cell and synaptic adhesion, homeostasis, and apoptosis. [6][7][8] APP is ubiquitously expressed as multiple splice variants, which undergo extensive post-translational modification. 9 Deposition of amyloid b peptide, a proteolytic product of APP, in senile plaques and in the walls of cerebral blood vessels is a hallmark of Alzheimer's disease.…”
Section: Introductionmentioning
confidence: 99%